THU0514 Fat but fit. the combined association of body mass indexand cardiorespiratory fitness with the fibromyalgia severity and tenderness: the al-Ándalus project. (12th June 2018) - Acosta-Manzano, P.; Gavilán-Carrera, B.; Segura-Jiménez, V.; Borges-Cosic, M.; García-Rodríguez, I.C.; Aparicio, V.A.
Abstract : Background: Since fibromyalgia is a complex widespread pain condition with large impact on physical and psychological health, 1 it is imperative to focus on modifiable factors that might decrease the impact of the disease on patients' lives. Accordingly, obesity and cardiorespiratory fitness (CRF) have been proposed as possible targets related to lower fibromyalgia severity and tenderness. 2, 3 However, based on the Fat but Fit Paradigm[, 4 no previous studies have examined if women with adverse body mass index (BMI) but high CRF, might present lower fibromyalgia severity and tenderness than those with non-adverse BMI and low CRF. Objectives: To examine the combined association of BMI and CRF with fibromyalgia severity and tenderness in women with fibromyalgia. Methods: A total of 433 women with fibromyalgia (51.8±7.5 years old) were included in this cross-sectional study. BMI was calculated and CRF was assessed with the 6 min walk test (6-MWT). The fibromyalgia severity and its components (function, overall impact and symptom severity) along with tenderness were assessed with the Revised Fibromyalgia Impact Questionnaire (FIQR) and algometry, respectively. BMI groups were stratified according to international criteria. Fit and unfit cut-offs were established according to the median value (fit ≥489 m, unfit <489 m in the 6-MWT). Analyses of covariance and Bonferroni post-hoc analyses were used to assess the combined association of BMI and CRF with FIQR variables and tenderness, and the differences of these outcomes variables between the groups created from the combination of the different levels of BMI and CRF, respectively. The potential confounders were age, occupational status, medication for relaxing or sleeping, and antidepressants. Results: Normal-weight and fit women showed better function, and lower overall impact and fibromyalgia severity than obese and unfit women (all, p≤0.05). Overweight but fit women showed better function, and lower overall impact and fibromyalgia severity than normal-weight and unfit women (all, p<0.01) or obese and unfit women (all, p<0.001). Additionally, overweight but fit women showed lower symptom severity than obese and unfit women (p<0.001). Obese but fit women experienced lower tenderness than normal-weight and unfit women (p=0.038). For the remaining analyses, differences of outcomes variables between groups were not statistically significant (p>0.05). Conclusions: The combination of BMI and CRF was significantly associated with the fibromyalgia severity and tenderness. Since overweight and obese fit women showed lower fibromyalgia severity and tenderness, it seems that the "Fat but Fit" paradigm might play an important role on fibromyalgia. These findings suggest that fitness might be able to counteract the adverse influence of obesity on fibromyalgia severity and tenderness. However, future physical exercise and dietary interventions are warranted to ascertain these findings. References: [1] Segura-Jimenez V, et al. Semin Arthritis Rheum2015Apr;44(5):563–570. [2] Segura-Jimenez V, et al. Eur J Pain2016May;20(5):811–821. [3] Soriano-Maldonado A, et al. Arthritis Care Res. 2015Nov;67(11):1561–1570. [4] Ortega FB, et al. CircRes2016May;118(11):1752–1770. Disclosure of Interest: None declared